Pengaruh Brand Ambassador, Brand Personality Dan Brand Image Terhadap Minat Pada Produk Scarlett Whitening (Studi Kasus Pada Konsumen Scarlett di Kota Malang) - Alfina, Rahmah; Wahono, Budi; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study was to determine and analyze the effect of brand ambassador, brand personality and brand image on buying interest in scarlett whitening products. Sampling was conducted on consumers in Malang City using the Maholtra formula so that a sample of 80 respondents was obtained. This research method uses multiple linear regression analysis with SPSS 25 analysis tools. This study shows that the influence of brand ambassadors, brand personality and brand image has a simultaneous effect on buying interest. In the t test (partial) brand ambassadors have no significant effect on buying interest while in the t test (partial) brand personality and brand image have a significant effect on buying interest. Keywords: Brand Ambassador, Brand Personality, Brand Image, Purchase Intention